Graphene Nanoflake- and Carbon Nanotube-Supported Iron–Potassium 3D-Catalysts for Hydrocarbon Synthesis from Syngas - Sergei A. Chernyak; Dmitrii N. Stolbov; Konstantin I. Maslakov; Ruslan V. Kazantsev; Oleg L. Eliseev; Dmitry O. Moskovskikh; Serguei V. Savilov (Nanomaterials, 2022)
Transformation of carbon oxides into valuable feedstocks is an important challenge nowadays. Carbon oxide hydrogenation to hydrocarbons over iron-based catalysts is one of the possible ways for this transformation to occur. Carbon supports effectively increase the dispersion of such catalysts but possess a very low bulk density, and their powders can be toxic. In this study, spark plasma sintering was used to synthesize new bulk and dense potassium promoted iron-based catalysts, supported on N-doped carbon nanomaterials, for hydrocarbon synthesis from syngas. The sintered catalysts showed high activity of up to 223 μmolCO/gFe/s at 300–340 °C and a selectivity to C5+ fraction of ~70% with a high portion of olefins. The promising catalyst performance was ascribed to the high dispersity of iron carbide particles, potassium promotion of iron carbide formation and stabilization of the active sites with nitrogen-based functionalities. As a result, a bulk N-doped carbon-supported iron catalyst with 3D structure was prepared, for the first time, by a fast method, and demonstrated high activity and selectivity in hydrocarbon synthesis. The proposed technique can be used to produce well-shaped carbon-supported catalysts for syngas conversion.